Habitats of the World Biodiversity and Threats - Maria Musarella, Carmelo; Cano Ortiz, Ana; Quinto Canas, Ricardo (IntechOpen, 2020)
Today it is not easy to talk about habitats and to think about the various threats facing them. We are living in an age in which we are poised between having everything immediately, and maintaining good living conditions on Earth. Unfortunately, this is almost impossible!For this reason it is important that everyone understands the importance of the habitats of the world and the inhabitants: including humans!This book aims to describe some of the world's habitats, their characteristics, and their daily threats. This is done in the hope that our children will see all of this tomorrow. Enjoy reading!